Implementasi Program Full Day School Dalam Meningkatkan Akhlak Peserta Didik - Siti Ainun Jariyah; Ishmatun Nihayah (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2021)
Full day school is a learning process program conducted a full day. Where student activities regarding the learning process are carried out more at school rather than at home, to avoid and minimize negative student activities after school. This study used field research which was classified into qualitative descriptive. The method of data collection used the interview, observation, and documentation. The method of data analysis used data reduction, data presentation, and concluding. After researchers conducted research at Pacet 1 Public Senior High School, the findings of researchers 1) Implementation of full day school programs in schools. The learning process starts at 6:45 a.m. to 3:30 p.m., taking breaks for two times. (b) the implementation of learning is carried out all day long for the interior and adding material, (c) the teaching staff and the placement of students in the morning class are differentiated in the afternoon class, (d) the implementation of learning in class is mostly carried out outside the classroom so that students do not get bored. 2) While the Implementation of the Full Day School Program in Improving the Morals of Students in Pacet 1 Public Senior High School, namely: (a) the addition and strengthening of religion wherein the material is directly related to morals, (b) the existence of superior programs such as: designed education Based on tawhid, education that is not limited to theory and which is easily applied by students in everyday life. (c) the methods used are: habituation method, exemplary, giving advice.